2013
DOI: 10.3201/eid1904.121572
|View full text |Cite
|
Sign up to set email alerts
|

Serotype IV and Invasive Group BStreptococcusDisease in Neonates, Minnesota, USA, 2000–20101

Abstract: Serotype predominance has shifted, and drug resistance is emerging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 35 publications
12
44
1
Order By: Relevance
“…The same scenario was observed among neonatal (2/64 cases; 3%) for the years 2000 to 2004 [12] and non-pregnant adult infections (2/225 cases; 1%) from 2001 to 2008 [14]. After 2010, reports from Brazil Ireland and the US [15][16][17][18] revealed an increased prevalence of serotype IV in colonisation and infection, suggesting the possibility that this serotype could be emerging as an important pathogen, as happened with serotype V during the 1990s [19].…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…The same scenario was observed among neonatal (2/64 cases; 3%) for the years 2000 to 2004 [12] and non-pregnant adult infections (2/225 cases; 1%) from 2001 to 2008 [14]. After 2010, reports from Brazil Ireland and the US [15][16][17][18] revealed an increased prevalence of serotype IV in colonisation and infection, suggesting the possibility that this serotype could be emerging as an important pathogen, as happened with serotype V during the 1990s [19].…”
Section: Introductionsupporting
confidence: 63%
“…This situation has changed in the last decade, when some countries, including the US, saw the emergence of serotype IV among colonising and invasive GBS isolates [15,16]. This scenario may become risky if the emergence of serotype IV combines with antibiotic resistance, which was the case in our study where co-resistance to second-line macrolide antibiotics was observed in recent years (2010-2012).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Type IV is recognized as an emerging cause of neonatal disease 33 . in infected human infants, will aid a full and mechanistic understanding of protective immunity in this age group.…”
Section: Immunization In Pregnancy and Placental Transfermentioning
confidence: 99%
“…For instance, the frequency of type V has increased in the last few years, whereas serotype IV has recently emerged as a cause of adult and neonatal invasive disease (8). Therefore, accurately monitoring the variation of this important target antigen is essential for predicting vaccine coverage.…”
mentioning
confidence: 99%